Analisis Faktor-Faktor Yang Mempengaruhi Jumlah Kemiskinan Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2006-2011 - Addina, Aninda Aula Zukhrufannisa, Dr. Daryono S., MEc, Ir. Maulidyah IH.,MS (2015)
Poverty is a fundamental problem that becomes the center of attention of the government in any country. In almost all developing countries, especially the standard of the population tends to be very low, one of which materialized in a very low level of income or poverty of life. One of the problems of development in Central Java is slow decline of poverty due to the lack of access to education, health, employment and capital. Another problem is ineffective agricultural productivity, livelihoods of poor farmers and the lack of control over the function of the shift of agricultural land into non-agricultural land. This study was conducted to determine the relationship between agriculture, economic growth, and population growth on poverty in Central Java. Both descriptive and econometric analysis has been carried out using fixed effects panel data from 35 districts / cities in Central Java, from 2006 to 2011. The results show evidence that the share of the agricultural sector and Gross Domestic Product significant effect or a positive effect in reducing poverty. On the other hand, industry and population has not been proven to reduce poverty effectively. Therefore, the government needs to take a policy of agricultural modernization through the development of agricultural technology, the provision of materials and means of production, as well as provide a market for agricultural products. Economic development based on SMEs (small and medium enterprises) and labor-intensive industries should be encouraged, to provide employment opportunities. The government also needs to ensure that the high economic growth can reach all levels of society. The government also needs to develop a technology that can improve the productivity of labor. In addition, population growth usually occurs in poor families still need to be controlled